Highly Flexible Transparent Electrodes Containing Ultrathin Silver for Efficient Polymer Solar Cells. (5th November 2015) - Ghosh, Dhriti Sundar; Liu, Quan; Mantilla‐Perez, Paola; Chen, Tong Lai; Mkhitaryan, Vahagn; Huang, Minghuang; Garner, Sean; Martorell, Jordi; Pruneri, Valerio
Abstract : Transparent electrodes (TEs) having electrooptical trade‐offs better than state‐of‐the‐art indium tin oxide (ITO) are continuously sought as they are essential to enable flexible electronic and optoelectronic devices. In this work, a TiO2 ‐Ag‐ITO (TAI)‐based TE is introduced and its use is demonstrated in an inverted polymer solar cell (I‐PSCs). Thanks to the favorable nucleation and wetting conditions provided by the TiO2, the ultrathin silver film percolates and becomes continuous with high smoothness at very low thicknesses (3–4 nm), much lower than those required when it is directly deposited on a plastic or glass substrate. Compared to conventional ITO‐TE, the proposed TAI‐TE exhibits exceptionally lower electrical sheet resistance (6.2 Ω sq −1 ), higher optical transmittance, a figure‐of‐merit two times larger, and mechanical flexibility, the latter confirmed by the fact that the resistance increases only 6.6% after 10 3 tensile bending cycles. The I‐PSCs incorporating the TAI‐TE show record power conversion efficiency (8.34%), maintained at 96% even after 400 bending cycles. Abstract : TiO2 /Ag/indium tin oxide (ITO)‐based transparent electrodes (TEs) with sheet resistance of 6.2 Ω sq −1 and average optical transmittance in the visible of 87.6% are developed. These performances are superior to those of state‐of‐the‐art single‐layer ITO. Polymer solar cells employing such TEs achieve 8.34% efficiency, higher than similar structures on conventional ITO.